Roma women's higher education participation: whose responsibility?. Issue 7 (3rd October 2018) - Hinton-Smith, Tamsin; Danvers, Emily; Jovanovic, Tanja
ABSTRACT: There are striking gaps between Roma and non-Roma higher education (HE) participation rates, with less than 1% of Roma possessing a tertiary-level qualification [United Nations Development Programme, World Bank and European Commission. 2011a. "The Situation of Roma in 11 EU Member States." Accessed 3 April 2015.http://issuu.com/undp_in_europe_cis/docs/_roma_at_a_glance_web/1#download ]. As the Decade of Roma Inclusion (2005–2015) closes, this renders the present a salient moment to reflect on Roma students' HE experiences. Widening educational access for marginalised groups raises specific questions about where responsibility for doing so lies – with tensions between individualised articulations of raising aspiration and notions of collective responsibility framed in a social justice agenda. Drawing on interviews with five Roma women students, this paper unpacks the contradictions between desiring access to HE for individual self-betterment and concurrent pulls towards educating for the wider benefit of 'improving' Roma communities. Using Ahmed's [2012. On Being Included: Racism and Diversity in Institutional Life . Durham, North Carolina: Duke University Press] work on institutional belonging, we explore the specifically gendered nature of these narratives in how 'doubly' marginalised bodies are positioned as outsiders, in receipt of an educational gift.